Parallelization algorithms on fine-grid segments in three-phase fluid flow problems - Gubajdullin, D.A.; Nikiforov, A.I.; Tsepaev, A.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2007)
The numerical parallelization algorithm earlier proposed by the authors for solving two-phase fluid flow problems is applied to solve a three-dimensional three-phase fluid flow problem on a coarse grid with fine-grid segments. This algorithm shows its efficiency with an increasing number of fine-grid segments. The numerical approximation of this problem is based on the control-volume method. The work was performed in the framework of Program N 14 for basic research established by the Presidium of the Russian Academy of Science under the title «Fundamental problems of computer science and information technologies».